Pengaruh Lingkungan Sekolah terhadap Motivasi Belajar Siswa Kelas XI Dalam Mata Pelajaran PAI di SMA Negeri 7 Sijunjung - Tahnia Mafatihul Khairah; Afrinaldi Afrinaldi; Salmi Wati; Deswalantri Deswalantri (Badan Penerbit STIEPARI Press, 2023)
The writing is motivated by the low learning motivation of class XI MIPA students at SMA Negeri 7 Sijunjung. Based on the results of observations, it can be see that the school environment at SMA Negeri 7 Sijunjung as a whole is in good condition. This is not in accordance with the theory which states that the more conducive the scool environment, the higher the student’s learning motivation. This research is a correlation research using a quantitative approach. The data collection technique in this study is to use a lift or questionnaire. The informants in this study were students of class XI MIPA at SMA Negeri 7 Sijunjung. Data analysis was carried out by means of normal traffic test, linearity test, hypothesis testing, and coefficient of determination test. Based on the results of the study it was found that the data in this study were normally distributed with a significance value of 0,200. This value indicates that the significant value is more than 0,05, which means that the data is normally distributed. From the results of the linearity test it is known that the significance value is 0,051 > 0,05, which means that there is a linear relationship between the school environment and students’ learning motivation. From the calculation results obtained rxy = 0,652 and rtabel = 0,234. With the testing criteria Ho is accepted if rxy ≤ rtabel and Ho is rejected if rxy ≥ rtabel. The results of the sampel hypothesis test with the pearson product moment correlation obtained a significance value of 0,652 ≥ 0,234, so it can be concluded that Ho is rejected and Ha is accepted. So it can be concluded that the hypothesis in this study is accepted, yes that there is an influence of the school environment on the learning motivation of class XI MIPA students at SMA Negeri 7 Sijunjung. Based on the test results of the coefficient of determination, the result is 0,425. So it can be concluded that the influence of the school environment on student learning motivation is 42,5%.